Food waste and loss management in HORECA: The 5C’s route guidance - Maria Torrejon Ramos; María-Sonia Medina-Salgado; Marta Ortiz-de-Urbina-Criado (Journal of Industrial Engineering and Management)
Purpose: The consumption of high levels of natural resources by Hotels, Restaurants and Catering -HORECA- has a significant impact on the environment. This paper examined the evolution of food waste and loss management in HORECA Supply Chain. Design/methodology/approach: A mixed methodology is used: bibliometric analysis with SciMat software and a narrative analysis, employing both quantitative and qualitative techniques. Findings: Authors devise a general model that encompasses the fundamental research areas: the context, internal and external stakeholders, approach, drivers, process management, product or service and results or performance. Furthermore, they present the 5C’s Route Guidance, which emphasises the importance of context, raising consciousness, identifying circular models by connecting the different stages of the supply chain, and creating sustainability-oriented methods, models and products, to collectively facilitate the reduction of food waste and loss. Research limitations/implications:  The article's academic implications include defining and positioning the core issues in HORECA supply chain management, providing future research questions, conceptual guidance, and advancing the theory of food waste reduction. On a practical level, it highlights the need to improve management in HORECA companies, raise awareness and call for collaboration between academia and professionals to advance practices to reduce food waste and loss from HORECA. Socially, the use of the 5C's Route Guidance can actively contribute to the achievement of the Sustainable Development Goals. Originality/value: To identify the current knowledge structure of a complex sector such as HORECA and its role for sustainability through the application of quantitative and qualitative methodologies. The findings aid researchers in achieving more robust studies, expanding the literature on the HORECA sector and its supply chain, and guiding them to focus their studies.